Intersectional factors between ethnicity, ADHD and dropout in upper secondary school in Iceland - Gloria Zarela Castro Conde 1978- (2018)
Studies show that a large percentage of children with multicultural backgrounds dropout of school in Iceland (Birgisdóttir, 2015). There are numerous and intersecting factors that influence this decision for students. Among these factors is the lack of academic and social support they receive during their school years. Research on Icelandic children between the ages of 7 and 15, who have an ADHD diagnosis has increased in the last few years, and a study conducted in 2007 shows that 5% of children were using psychotropic drugs, which could be a further factor in dropping out. To date, there is no research in Iceland that indicates if a diagnosis like ADHD contributes to the rate of immigrant student dropout. These factors need further analysis. My paper is an attempt to understand how an ADHD diagnosis can impact immigrant student retention rates in Icelandic schools. With the continued increase in the number of multicultural children in the schools, the need is great for better implementation of theory and practice in inclusive education to benefit all students.